'Defeatism is Our Worst Enemy'Rehabilitation, Reorientation and indonesianisasi at Internatio and RVA, 1945-1958 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRAK After Dutch recognition of Indonesian soversignty in Desember 1949, the Indonesian economy continued to be dominated by foreign mainly Dutch enterprise. This paper looks in detail at the Rotterdam trading firm Internatio and